In vivo imaging of the mouse cholinergic projection system using [18F]FEOBV. (20th December 2022) - Onuska, Kate M.; Shanks, Hayley R. C.; Qi, Qi; Prado, Vania; Thiessen, Jonathan; Hicks, Justin; Fox, Matthew; Prado, Marco; Schmitz, Taylor W.
Abstract: Background: Positron emission tomography (PET) with the [ 18 F]‐Fluoroethoxybenzovesamicol ([ 18 F]FEOBV) radiotracer is a promising tool for in vivo imaging of VAChT – a protein found specifically in the cholinergic system. However, the sensitivity and specificity of [ 18 F]FEOBV uptake to known changes in VAChT protein levels remains untested. The aim of this study is therefore to use [ 18 F]FEOBV in mouse lines where VAChT protein expression is held under precise genetic control to determine whether [ 18 F]FEOBV brain uptake reflects the endogenous levels of VAChT present in different genetic mouse models. Method: 6‐month‐old VAChT conditional forebrain knock‐out mice (VAChT Nkx2.1‐Cre‐flox/flox, n = 6), VAChT hyper expressing mice (VAChT ChAT‐ChR2‐eYFP, n = 6), and littermate controls (VAChT flox/flox, n = 6; C57BL/6J, n = 6), received an intravenous injection of [ 18 F]FEOBV and were imaged dynamically on a microPET scanner for 2 and a half hours. Result: When compared to controls, VAChT conditional forebrain knock‐out mice demonstrated decreased [ 18 F]FEOBV uptake in striatal regions of the mouse brain (Figure 1, left panel). In contrast, VAChT hyper expressing mice displayed widespread increases in brain [ 18 F]FEOBV uptake when compared to controls (Figure 1, right panel). Conclusion: Together, these findings suggest that [ 18 F]FEOBV brain uptake is a sensitive and specific measure of known changes in VAChT protein expression.